G168 HPV: not just for girls! a qualitative study exploring the views of 11–12 year olds about the human papillomavirus (HPV) vaccination. (25th October 2020) - Williamson, E; Forster, A; Bedford, H
Abstract : Background: Since 2008, human papillomavirus vaccine (HPV) has been offered to 12–13 year old girls in the UK to prevent infection that can lead to cervical cancer. Vaccine uptake in this schools based programme is generally very high. From September 2019, boys will also be offered the vaccine to reduce the burden of HPV-related disease in men. Little is known about boys' knowledge of HPV infection and attitudes towards the vaccine. This study aimed to explore 11–12 year old girls' and boys' understanding of HPV infection and their views about the vaccine. To assess their information requirements, their views of the content and appearance of draft HPV leaflets developed by Public Health England were also sought. Methods: Using a qualitative approach, four single-sex focus group discussions were conducted in two secondary schools. Discussions were audio recorded and transcribed using a thematic approach. Results and Conclusions: Thirteen girls and twelve boys took part in four focus groups. Emerging themes included vaccine views, knowledge and awareness of HPV infection, HPV vaccination programme knowledge and acceptability, receiving information about HPV and HPV vaccination. Awareness and knowledge of HPV infection and vaccination was low among all participants. Acceptability of HPV vaccination was high, especially after participants' questions and concerns were addressed through explanations. There was unanimous desire for accessible information before being offered the vaccine, using a combination of leaflets and face-to-face education from professionals, to enable participants to make an informed decision about vaccination. Participants primarily wanted information about the benefits of vaccination and potential adverse effects. The findings of this study highlight important areas that should be addressed by HPV information materials directed towards adolescents. Future research could evaluate the influence of different educational interventions in UK schools on knowledge and acceptability of the HPV vaccine.